NAMOD: A Namibian tax-benefit microsimulation model - Gemma Wright; Michael Noble; Helen Barnes (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper provides an account of the construction of a tax-benefit microsimulation model for Namibia (NAMOD) which is based on the EUROMOD platform F6.0. Previous research on social security provision in Namibia is reviewed and the current social security, personal income tax and value added tax arrangements are outlined. Various strengths and weaknesses of the Namibian Household Income and Expenditure Survey (NHIES) as an underpinning dataset for NAMOD are highlighted. In particular, the income data in the NHIES is problematic and so analysis of the impact of policies on poverty should be treated with caution. In spite of these challenges, NAMOD provides a starting point from which government can explore issues such as promoting take-up of grants or making changes to the social security system.
Keywords: I32; I38; H55; 330; tax-benefit policy; microsimulation; developing country; Namibia